Map2k5-Deficient Mice Manifest Phenotypes and Pathological Changes of Dopamine Deficiency in the Central Nervous System - Huang, Yumeng; Wang, Pei; Morales, Rodrigo; Luo, Qi; Ma, Jianfang (Frontiers in Aging Neuroscience, 2021)
MAP2K5, a member of MAPK family, is associated with central nervous system disorders. However, neural functional of Map2k5 from animal models were not well examined so far. Here, we established a Map2k5 targeted knockout mouse model to investigate the behavior phenotypes and its underlying molecular mechanism. Our results showed that female Map2k5 mutant mice manifested decreased circadian-dependent ambulatory locomotion, coordination and fatigue. Male Map2k5 mutant mice displayed impairment in open field exploration and prepulse inhibition of acoustic startle response when compared to wild type controls. Furthermore, Map2k5 mutant mice showed a decreased dopaminergic cells survival and tyrosine hydroxylase levels in nigrostriatal pathway, indicating a crucial role of MAP2K5 in regulating dopamine system in the central nervous system. In conclusion, this is the first study demonstrating that Map2k5 mutant mice displayed phenotypes by disturbing the dopamine system in the central nervous system, implicating Map2k5 mutant mouse as a promising model for many dopamine related disorders.